AIDS, Antiretrovirals, Brazil and the International Politics of Global Health, 1996–2008. (11th July 2019) - Cueto, Marcos; Lopes, Gabriel
Summary: In the mid-1990s, Brazil became a player in the global politics of AIDS through its participation in debates on whether antiretroviral drugs were commodities or public goods. Brazilian actors not only challenged powerful pharmaceutical companies but the assumption that international health policies were solely defined in developed countries. After 1996, a coalition of Brazilian officers, health activists, people living with Aids and medical scientists advocated for universal access to generic medication (instead of costly patented drugs) and publicized its achievements at home and abroad, such as a marked decline in AIDS cases. However, during the first decade of the twenty-first century increased costs, little attention to prevention and the persistence of homophobia hindered treatment. Moreover, unilateral US programmes and conservative evangelicals glorifying sexual abstinence sabotaged anti-AIDS work. After the financial crisis of 2008, universal access to ARVs lost political momentum and sustaining treatment became difficult in Brazil.